The impact of the entrepreneur’s profile on the entrepreneurial failure of Moroccan very small business - Elafi, Reda; Jouali, Youssef; Wahbi, Aumaima (Edelweiss Applied Science and Technology, 2024)
This article addresses a crucial and timely question: What are the critical factors in the entrepreneur’s profile that contribute to the failure of small Moroccan companies? To answer this question, this study seeks to meticulously analyze the failed entrepreneur’s profile characteristics, drawing upon a myriad of previous academic studies. The present study study is based on data from a 2022 survey, which achieved a response rate of approximately 40%. The study utilizes a logistic regression model to test our hypothesis. Of significant importance are the findings of this study which reveal that an entrepreneur is more likely to witness company failure if he is a man under 35, driven by the need for income, and has established a SARL business.